Human Security in Asia: Interrogating State, Society, and Policy, edited by Debasish Nandy, and Debtanu Majee. Palgrave Macmillan, Singapore, 2024. XXI, 346 pp. https://doi.org/10.1007/978-981-99-3585-7 - Viktorya Melkonyan (Journal of Political Science: Bulletin of Yerevan University)
This book comparatively analyzes the relationship between human security and national security from the theoretical perspective of the transition from traditional security to human security. The different chapters of this book analyze the structured and organized dimensions of human security that shed light on the economic, food, health, community, environment and political security conditions in Asian countries. The authors explore the theoretical foundations and various models of human security to understand the challenges threatening human security of Asian countries. This book also analyzes the different situations of Asian countries where economically vulnerable and politically unstable and sometimes broken political systems are unable to easily address the problems of hunger, poverty, illiteracy, militancy, terrorism and ethno-religious conflicts that pose a real threat to human security. The book discusses the challenges of health policies in Asian countries in the wake of the COVID-19 pandemic, which has led to a major humanitarian crisis, taking into account the limited role of Asian countries in combating COVID-19. It is important to note that this book develops an interdisciplinary discourse on human security among scholars not only in Asian countries but also throughout the world.